The first outbreak of herpes gladiatorum in Thailand: an investigation of boxing gyms in Phuket, May–August 2022 - Srisaeng, Suppasit; Swangpun, Kusuma; Panchaiyaphum, Arriya; Okada, Pilailuk Akkapaiboon; Sornsurin, Warodom; Naraart, Panuwat; Chantian, Thanawadee (Western Pacific Surveillance and Response, 2025)
Objective: The objectives of this study were to describe the characteristics of Thailand’s first reported outbreak of herpes gladiatorum in Thai-boxing gyms and to provide recommendations for reducing the risk of transmission. Methods: Hospital reports of atypical rashes appearing among Thai-boxing trainees triggered investigations at three gyms in Phuket during May–August 2022. Semistructured questionnaires were used to collect data from gym owners, trainers and trainees. Skin and blood specimens were collected for reverse transcription–polymerase chain reaction testing for herpes simplex virus type 1 (HSV-1), antibodies to HSV-1 and other pathogens; genomic sequencing was performed on culturable samples. The environmental investigation included walk-through surveys, a review of each gym’s web site, and testing of surfaces and water specimens. Results: Nine cases of herpes gladiatorum were confirmed and one was suspected, all in non-Thai trainees. Attack rates in Gyms I, II and III were 21.4%, 11.5% and 2.6%, respectively. Risk behaviours included sparring with partners who had a rash, sharing equipment and neglecting to shower before training. HSV-1 was detected on gym equipment and surfaces, and cultures from skin lesions and blood samples revealed a genomic linkage between two cases in Gym II, identified as belonging to the East Asian Clade II strain. Disinfection of equipment reduced exposure to HSV-1. Discussion: The first outbreak of herpes gladiatorum in Thailand was confirmed in 2022. Genomic sequencing suggested local transmission within Thailand, with the virus introduced independently into each gym. Skin-to-skin contact was likely the main mode of transmission; environmental findings indicated a lower risk of transmission via gym surfaces. Recommendations to prevent future outbreaks include stricter regulations for pre-fight screening and improved gym cleaning and hygiene among trainers and trainees.